Comparison of the gut content of the Indian squid Photololigo duvaucelii (d'Orbigny, 1835) and the sword squid Photololigo edulis (Hoyle, 1885) ( Mollusca cephalopoda) from Conception, Iloilo. - Tingson, Czarra Jade E.
Despite their short life cycles, cephalopods are one of the most diverse and well-distributed marine animals throughout the world, greatly contributing to fishery as alternatives when fishes are overexploited. Squids function as both predator and prey, havingtremendous effect in the marine food web. This study analyzed Photologo edulis and Photoligo duvaucelii of different size classes, harvested in May 2018, to analyze their stomach contents and explain their prey preference and feeding behavior. 60 squid samples, with 30 individuals each species were examined, separated to size classes of mantle length (ML) with 1 cm increments. Ratio of chime and non-chyme between the two species are different but deemed not significant, P. edulis had more chyme (59%) over non-chyme (41%), and P. duvaucelii had more non-chyme component (60%) than chyme (40%). The prey items in the two species were the same categories, namely: Teleosts, crustaceans, and cephalopods, and cannibalism is speculated. In P. duvaucelii the largest chunk are the crustaceans (56.3%) followed by fishes (32.9%) and then cephalopods (9.5%), while P. edulis had fishes in an outstanding frequency (64.9%), crustacean (21.9%) and then cephalopods (11.6%). Algae was also observed to be present in some of the guts of both species. Samples with smaller ML prey on crustacean then switching to fish and cephalopods as they grow larger. Feeding habit is highly correlated with their size classes and not their differences as a species. Further studies such as comparison in spatial (different harvesting grounds) and temporal (month or year of capture) can be done, to analyze how these can affect prey preference in order to foresee how fishing and anthropogenic factors can influence their abundance and distribution in the ocean.